2019
DOI: 10.1002/uog.20411
|View full text |Cite
|
Sign up to set email alerts
|

Revised competing‐risks model in screening for pre‐eclampsia in twin pregnancy by maternal characteristics and medical history

Abstract: Background We have proposed previously that the competing‐risks model for prediction of pre‐eclampsia (PE) based on maternal characteristics and medical history (prior model), developed in singleton pregnancies, can be extended to risk assessment for twins; in dichorionic (DC) and monochorionic (MC) twin pregnancies with the same characteristics as in singleton pregnancies, the distribution of gestational age at delivery with PE was shifted to the left by 8 and 10 weeks, respectively. However, in a subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In previous studies investigating the value of screening for PE by a combination of maternal demographic characteristics and medical history with biomarkers in the first, second and third trimesters in singleton and twin pregnancies, the outcome measure was PE as defined originally by the ISSHP 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . In the first trimester, screening has been achieved successfully by a combination of maternal demographic characteristics and medical history, uterine artery pulsatility index (UtA-PI), mean arterial pressure (MAP) and serum placental growth factor (PlGF) through application of the competing-risks approach [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies investigating the value of screening for PE by a combination of maternal demographic characteristics and medical history with biomarkers in the first, second and third trimesters in singleton and twin pregnancies, the outcome measure was PE as defined originally by the ISSHP 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . In the first trimester, screening has been achieved successfully by a combination of maternal demographic characteristics and medical history, uterine artery pulsatility index (UtA-PI), mean arterial pressure (MAP) and serum placental growth factor (PlGF) through application of the competing-risks approach [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In the assessment of risk for PE in twin pregnancy, we can use the same prior model based on maternal characteristics and medical history as reported previously 10 , but in the calculation of posterior risks it is necessary to use the new distributions of log 10 MoM values of UtA-PI, MAP and PlGF according to gestational age at delivery with PE.…”
Section: Discussionmentioning
confidence: 99%
“…We used the dataset from the EVENTS trial 12 to validate the previously reported prior model for prediction of PE by maternal characteristics and medical history 10 . Calibration was assessed visually by plotting the observed incidence against that predicted for delivery with PE at < 32 and < 37 weeks' gestation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations